Estudo do amaciamento de um aço ultrabaixo carbono microligado ao titânio após deformação a quente e a morno - Jônatas Venancio Barbosa (2019)
The metallurgical phenomena occurring in the hot rolling process and the mechanical properties of the final product can be modified by changes in the steel thermomechanical processing, such as the ferritic rolling or warm rolling. In this sense, an investigation of the mechanical and metallurgical behavior of a titanium added ultralow carbon steel was performed during hot and warm deformation. Compression tests were performed in a thermomechanical simulator (dilatometer) using single and double hit schedules at temperatures between 650°C and 1050°C, and inter-pass times between 0,5 and 100 s, studying the softening behavior of the steel. The microstructure evolution was evaluated in some processing conditions by optical microscopy. The phase transformation mapping was performed by inflection points analysis in curves of dimensional variation versus temperature, and mean flow stress versus temperature, showing similar results. In general the steel showed a dynamic recovery behavior. Only the deformations in the intercritical region produced flow curves decrease after a peak tension. Isothermal holding tests associated with single hit compression attributed this tension flow drop behavior with the presence of dynamic strain induced transformation in the intercritical region. The static softening evolution was measured, indicating short period for beginning of recrystallization in austenitic field. A high softening kinetics in intercritical region was associated with ferrite formation in the inter-pass time. Decreasing the temperature to the ferritic field, static recovery prevailed, with much lower kinetics. Indications of strain induced boundary motion were found in microstructures also in the ferritic region. Finally it was performed a simulation of the hot strip mill process with deformation in the ferritic region, where it was proposed process temperatures to the practice of warm rolling.